Relationship between lower limb power output, sprint and change of direction performance in soccer players - Monika Papla; Agata Latocha; Wojciech Grzyb; Artur Golas (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2022)
Introduction: Although soccer matches require players to perform repetitive power-related abilities, the impact of lower-body strength and power asymmetry on sprint and change of direction (COD) performance receives little attention. Therefore, this study aimed to establish the relationship between lower limb power, sprint, and change of direction (COD) performance. In addition, the relationship between lower limb power asymmetry and the above mentioned running tests was determined. Material and Methods: Twenty-four male soccer players from First Polish League (age = 24.8 ±8.2 years, body mass = 77.4 ±16.9kg, body height=179.5 ±14.5cm, soccer training experience = 10 ± 1.5years) took part in the study. To examine the relationship between linear sprint, lower limb muscle power, and COD performance (time and deficit), the following tests were performed: 5-and 20-m linear sprint, leg press exercise, and two 20-m COD sprints ("COD90" and "L" test). Result: Pearson correlation coefficients didn't show any statistically significant relationship between lower limb power and linear sprint speed as well as COD performance. The results indicate that the considered variables are independent physical characteristics. Conclusion: Relative lower limb-power output and low level of mean inter-limb asymmetry in power output does not affect 5- and 20-m linear sprint time and COD performance with 90° turn.